2020
DOI: 10.1111/josh.12904
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Disorder and Internalizing Problems Among Swedish Adolescents: Changes Between 1988 and 2011

Abstract: BACKGROUND Internalizing problems have increased among Swedish adolescents. We examined whether classroom disorder was associated with internalizing problems and whether it explained the trends in internalizing problems. Furthermore, we examined whether school contextual factors were associated with internalizing problems and whether they moderated the association between classroom disorder and internalizing problems. METHODS We used repeated cross‐sectional survey data (1988‐2011) among all 15‐ to 16‐year‐old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Parents' warmth is directly positively related to their perceptions of children's agency, which in turn were related to lower child externalising and internalising problems and higher academic achievement (Gurdal et al, 2016). Other longitudinal research in Sweden has shown that children's perception of school disorder is associated with more internalising problems (Evans et al, 2020) and that mothers' previous and current depressive symptoms increase the risk of child behaviour problems in 12‐year‐olds (Agnafors et al, 2013).…”
Section: Cultural Values In Swedenmentioning
confidence: 99%
“…Parents' warmth is directly positively related to their perceptions of children's agency, which in turn were related to lower child externalising and internalising problems and higher academic achievement (Gurdal et al, 2016). Other longitudinal research in Sweden has shown that children's perception of school disorder is associated with more internalising problems (Evans et al, 2020) and that mothers' previous and current depressive symptoms increase the risk of child behaviour problems in 12‐year‐olds (Agnafors et al, 2013).…”
Section: Cultural Values In Swedenmentioning
confidence: 99%